2015
DOI: 10.1039/c5ta01321f
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of CO2 on a micro-/mesoporous polyimine modified with tris(2-aminoethyl)amine

Abstract: 5Amine-modified sorbents are relevant to the capturing of dilute carbon dioxide from gas mixtures, and micro-/mesoporous polymers are promising substrates due to their rich chemistry. Here, we prepared an aldehyde-rich polyimine with micro-and mesopores with a Schiff-base condensation of 1,3,5-tris(4aminophenyl)benzene and 1,3,5-benzenetricarboxaldehyde using an excess of aldehydes. The micropores were crucial to the physisorption of CO 2 , while the mesopores provided space for the post-modification 10 with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 56 publications
0
41
1
Order By: Relevance
“…Noteworthy, for the NACs, the uptake of CO 2 at a pressure of 0.2 bar is relatively high (2.7, 2.5 and 2.0 mmol g −1 at 273 K for NAC-800, NAC-700 and NAC-600 respectively). NAC-800 surpasses most porous carbons and is comparable with some high performing sorbents under the same or similar conditions (0.2 bar), such as NMC-800 (2.5 mmol g −1 )29, PP1-2 (1.5 mmol g −1 )26, AC (1.5 mmol g −1 )30 and CS3-A6 (2.6 mmol g −1 )31. It competes with the porous carbon materials and was comparable with some top performing CO 2 adsorption such as NMC-800 (2.5 mmol g −1 )29, NPC-650 (2.4 mmol g −1 )18, MR-1-500 (2.2 mmol g −1 )30.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…Noteworthy, for the NACs, the uptake of CO 2 at a pressure of 0.2 bar is relatively high (2.7, 2.5 and 2.0 mmol g −1 at 273 K for NAC-800, NAC-700 and NAC-600 respectively). NAC-800 surpasses most porous carbons and is comparable with some high performing sorbents under the same or similar conditions (0.2 bar), such as NMC-800 (2.5 mmol g −1 )29, PP1-2 (1.5 mmol g −1 )26, AC (1.5 mmol g −1 )30 and CS3-A6 (2.6 mmol g −1 )31. It competes with the porous carbon materials and was comparable with some top performing CO 2 adsorption such as NMC-800 (2.5 mmol g −1 )29, NPC-650 (2.4 mmol g −1 )18, MR-1-500 (2.2 mmol g −1 )30.…”
Section: Resultsmentioning
confidence: 67%
“…synthesized hierarchical macroporous N-doped carbons (MCN) with ordered three-dimensional periodic structures25. However, CO 2 is expected to interact robustly with high polar imines functionalities in the polymer26. Gas adsorption and desorption of porous materials depend not only on the high specific surface area, micropore volume or pore size but also on the chemical composition and structural features of the materials27.…”
mentioning
confidence: 99%
“…[15][16][17][18] It has been revealed that the properties of polymer depend mainly on the polymer architecture as well as the intrinsic properties of synthons. For example, the polymers comprising of larger conjugated system is of benefit to the adsorption of H 2 19,20 as well as the fluorescent detection of Nitro-benzene derivatives, while the polymers with large N content usually exhibits promoted adsorption affinity toward CO 2 .…”
mentioning
confidence: 99%
“…By aldehyde excess, we have recently shown that the aldehyde end groups of the PPs could further be modified by tetramines and form amine-rich chemisorbents for CO 2 [16]. Other effects deviating from a stoichiometric balance were shown by Schmidt et al The monomer-ratio used affected the polymer networks, surface areas and porosities of the polymers [41].…”
Section: Spectroscopic Studiesmentioning
confidence: 91%
“…For such applications, micropores as well as mesopores are advantageous. We recently studied micro-mesoporous polyimines as substrates for cooperative organopalladium catalysis [15] and as substrates for tethering tetramines when developing CO 2 chemisorbents [16]. In this study, we detail how the micro-and mesoporosity can be controlled in such polyimines and how that effects the physisorption of CO 2 .…”
Section: Introductionmentioning
confidence: 99%